Causal Structure of Opsen Implementation, Human Resource Capacity, and Local Own-Source Revenue Optimization - Chandra Meida Dewi; Alexandra Hokum; Benius Benius (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Local governments in Indonesia increasingly adopt digital fiscal innovations to enhance local own-source revenue. The opsen application integrates the collection and reporting of motor vehicle tax and vehicle title transfer fee into regional financial systems. However, despite its implementation across all districts and cities, local own-source revenue performance remains uneven, suggesting that technology alone is insufficient and highlighting the need to examine the role of human resource capacity in optimizing fiscal digitalization. This study aims to analyze the relationships between opsen implementation, human resource capacity, and local own-source revenue optimization. Using a quantitative explanatory approach, data were analyzed with SPSS to examine correlations, regression, and mediating effects among variables. The results indicate that opsen implementation has a significant positive effect on local own-source revenue optimization, both directly and indirectly through human resource capacity. These findings confirm that human resource capacity plays a strategic mediating role in ensuring the effective utilization of fiscal technology. This study contributes to the literature on digital public finance by demonstrating that technological innovation must be accompanied by strong institutional and human resource capacity. The findings provide evidence-based policy recommendations for strengthening local government capacity and enhancing the sustainability of regional fiscal digitalization.